A case report of childhood onychomycosis caused by the rare yeast Kodamaea ohmeri - Thi Minh Chau Ngo; Dong Duong Ton That; Phuong Anh Ton Nu; Le Chi Cao; My Nguyen Thi Tra; Thi Quynh Trang Tran (Medical Mycology Case Reports)
Onychomycosis is an uncommon disease in pediatric patients with dermatophytes and Candida spp. being the main causative agents. Kodamaea ohmeri has recently emerged as a human pathogen, including an onychomycosis causative agent. Here, we report the first case of childhood onychomycosis caused by K. ohmeri in Vietnam, presenting clinically as a white superficial onychomycosis. Fungal identification was confirmed by sequencing of the ITS1-2 region. Antifungal susceptibility testing revealed low minimum inhibitory concentrations for all tested agents, except fluconazole and caspofungin. The patient was treated with 2 % ketoconazole cream one month, resulting in complete resolution of the nail damage with no relapse observed after six months.